Evaluation of scoring methods in trauma patients with rib fractures - Cakmak, Muharrem (Bayrakol Medical Publisher, 2022)
Aim: In thoracic traumas, it is very important to provide accurate treatment after determining the severity of the trauma. Therefore, scoring systems are used to determine morbidity and mortality rates. These scoring methods include the Rib Fracture Score (RFS), Chest Wall Injury Score (CWIS), Chest Trauma Score (CTS), Thoracic Trauma Severity Score (TTSS), and Injury Severity Score (ISS). In our study, we aimed to evaluate the scoring systems in patients with post -traumatic rib fractures and accompanying pathologies, and to determine the trauma severity, mortality and morbidity rates with these scorings.Material and Methods: The records of 482 patients followed up and treated for post-traumatic rib fractures. The patients were divided into two groups as survivors (n: 418) and those who died (n: 64). The mean number of fractures, RFS, CWIS, CTS, TTSS, ISS values, and mortality and morbidity rates were recorded.Results: The mean number of fractures was 3.02 +/- 2.92, RFS; 4.84 +/- 4.71, CWIS; 1.68 +/- 0.79, CTS; 5.01 +/- 1.46, TTSS; 6.58 +/- 2.20, ISS; 7.90 +/- 8.64. When surviving and deceased patients were compared in terms of the mean number of fractures, RFS, CWIS, CIS, TTS, and ISS, the number of deceased patients was statistically significant compared to the surviving patients (p<0.05).Discussion: It was observed that mortality rates increased in trauma patients as the number of rib fractures increased with concomitant pathologies such as pneumomediastinum, hemothorax, pneumothorax, contusion, and flail chest as well as concomitant organ injuries such as spleen, kidney and liver. These pathologies and the presence of concomitant injuries were significant in mortality and morbidity.
Keywords: Fractures; Ribs; Scoring; Trauma